Exploring the efficacy and tolerability of two‐injection start regimen of long‐acting aripiprazole: A descriptive case series analysis - Ibrahim Sungur; Kaan Keskin; Elif Özge Aktaş; Mehmet Çağdaş Eker (Wiley, 2024)
Abstract Bipolar disorder is the fourth most debilitating psychiatric illness in the world regarding Disability Adjusted Life Years and manic episodes frequently lead to lengthy hospitalizations which restricts the freedom of patients. Therefore, decreasing the length of hospitalization with safer agents is of utmost importance in the treatment of manic episodes. Aripiprazole is a medication known for its efficacy in managing mania associated with bipolar disorder. Aripiprazole long‐acting injection is approved for the treatment of mania associated with bipolar disorder in adults and found efficacious as a maintenance treatment. In the treatment of schizophrenia, European Medicines Agency has approved a simplified starting strategy of aripiprazole once a month, with two 400 mg injections and a single oral 20 mg dose of aripiprazole. To the best of our knowledge, no previous study has reported the safety, tolerability, and efficacy of this regimen in adult bipolar disorder patients. We present a case series of eight patients who were admitted to the hospital in a manic episode with psychotic features. We observed that the double injection start regimen was effective in treating manic symptoms with no specific severe adverse events. We conclude from a small sample of manic patients that a double injection start regimen has good efficacy and tolerability.